2023
DOI: 10.1097/rlu.0000000000004652
|View full text |Cite
|
Sign up to set email alerts
|

68Ga-FAPI PET/CT Provides a Clear Picture of a Klatskin Tumor That 18F-FDG PET/CT Missed

Abstract: Klatskin tumor, also known as hilar cholangiocarcinoma, was clearly demonstrated in this case report by contrasting 68Ga-FAPI and 18F-FDG PET/CT in the same patient. This instance exemplifies a false-negative 18F-FDG PET/CT for the main tumor site, despite positive 68Ga-FAPI uptake at the same location.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…Studies have shown that FAPI PET imaging is particularly superior to FDG for detecting tumors with a strong desmoplastic reaction, such as breast, colon, hepatobiliary, gastrointestinal, pancreatic, sarcomatous, and rare neoplasms, making it a potential rival to FDG imaging in several lethal cancer subtypes. 7 8 9 Ongoing research will continue to explore the potential of FAPI imaging in various cancer subtypes, and clinical trials are being conducted to assess its safety and efficacy as a therapeutic tool in the coming years. 10 …”
mentioning
confidence: 99%
“…Studies have shown that FAPI PET imaging is particularly superior to FDG for detecting tumors with a strong desmoplastic reaction, such as breast, colon, hepatobiliary, gastrointestinal, pancreatic, sarcomatous, and rare neoplasms, making it a potential rival to FDG imaging in several lethal cancer subtypes. 7 8 9 Ongoing research will continue to explore the potential of FAPI imaging in various cancer subtypes, and clinical trials are being conducted to assess its safety and efficacy as a therapeutic tool in the coming years. 10 …”
mentioning
confidence: 99%
“…Studies have shown that FAPI PET imaging is particularly superior to FDG for detecting tumors with a strong desmoplastic reaction, such as breast, colon, hepatobiliary, gastrointestinal, pancreatic, sarcomatous, and rare neoplasms, making it a potential rival to FDG imaging in several lethal cancer subtypes. [7][8][9] Ongoing research will continue to explore the potential of FAPI imaging in various cancer subtypes, and clinical trials are being conducted to assess its safety and efficacy as a therapeutic tool in the coming years. 10 Despite their potential benefits, FAPI imaging faces inherent challenges and limitations.…”
mentioning
confidence: 99%
“…Cholangiocarcinoma has been studied previously using 68 Ga-FAPI PET/CT and was found to have a high 68 Ga-FAPI avidity, exceeding SUV max values of 12. 1,2 A recent retrospective study analyzed a group of 19 patients with pancreatic adenocarcinoma and found that 68 Ga-FAPI was successful in differentiating benign from malignant disease using differential uptake kinetics. 3 In addition, 68 Ga-FAPI PET/CT was found to be superior to conventional imaging modalities in restaging and detecting recurrent disease in half of the patients.…”
mentioning
confidence: 99%
“…The SUV max was calculated for the primary tumor site and found to be 14.7. Cholangiocarcinoma has been studied previously using 68 Ga-FAPI PET/CT and was found to have a high 68 Ga-FAPI avidity, exceeding SUV max values of 12 1,2 . A recent retrospective study analyzed a group of 19 patients with pancreatic adenocarcinoma and found that 68 Ga-FAPI was successful in differentiating benign from malignant disease using differential uptake kinetics 3 .…”
mentioning
confidence: 99%

68Ga-FAPI PET/CT Imaging

Al-Ibraheem,
Abdlkadir,
Alalawi
et al. 2023
Clin Nucl Med
Self Cite